(untitled) (Research, Society and Development, 2021)
Dental fluorosis results from the ingestion of small amounts of fluoride over a long period of time, which can affect mineralized tissues, bone and tooth enamel. The critical period occurs from 15 to 30 months, when the permanent incisors are in transition between the secretory phase and the enamel maturation phase. The purpose of this article is to report a clinical case presenting the enamel microabrasion technique as an effective treatment option for dental fluorosis classified as moderate: Case report. The correct diagnosis is extremely important for the indication and success of the treatment. The microabrasion of the dental enamel was sufficient and solved the patient’s aesthetic problem quickly and safely. It is recommended to use this technique when the diagnosis is alteration due to mild to moderate fluorosis.